2021
DOI: 10.1111/jam.15227
|View full text |Cite
|
Sign up to set email alerts
|

Indole decreases the virulence of pathogenic vibrios belonging to the Harveyi clade

Abstract: Aim: Indole is a signaling molecule secreted by over 85 species of bacteria, including several Vibrio species, and it has been reported to affect different bacterial phenotypes such as biofilm formation, motility, and virulence. In this study, we aimed at investigating the inter-strain variability of the effect of indole in 12 different strains belonging to the Harveyi clade of vibrios. Methods and Results:Indole reduced the virulence of all strains towards gnotobiotic brine shrimp larvae. The survival rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 68 publications
(86 reference statements)
1
21
1
Order By: Relevance
“…In addition, halogenated indoles have been reported to have nematicidal and insecticidal potential ( 34 , 35 ). Although the antivirulence activity of indole in V. campbellii has been reported in our previous work ( 23 , 36 ), the concentration at which the best virulence-inhibitory activity occurred was also toxic to invertebrates.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…In addition, halogenated indoles have been reported to have nematicidal and insecticidal potential ( 34 , 35 ). Although the antivirulence activity of indole in V. campbellii has been reported in our previous work ( 23 , 36 ), the concentration at which the best virulence-inhibitory activity occurred was also toxic to invertebrates.…”
Section: Introductionmentioning
confidence: 59%
“…Therefore, it is desirable to select antimicrobial agents with the ability to decrease biofilm formation. It has been reported before that indole inhibited biofilm formation in V. campbellii , V. harveyi , and V. parahaemolyticus at a relatively high concentration of 200 μM ( 23 ), and 6-fluoroindole can inhibit bacterial biofilm formation in S. marcescens at a concentration of 250 μM ( 33 ). Interestingly, 4-fluoroindole and 7-fluoroindole were shown to decrease biofilm formation at lower concentrations of 20 μM and 100 μM in Candida albicans and S. marcescens ( 30 , 42 ), whereas neither of them affected biofilm formation of V. campbellii in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indole is produced from tryptophan by tryptophanase (TnaA) in a large number of Gram‐positive and Gram‐negative bacterial species, including V. campbellii (Deeley & Yanofsky, 1981 ; Lee & Lee, 2010 ; Yang et al, 2017 ). It controls diverse aspects of bacterial physiology, such as spore formation (Kim et al, 2011 ), plasmid stability (Chant & Summers, 2007 ), drug resistance (Vega et al, 2012 ; Zhang et al, 2020 ), biofilm formation (Lee, Jayaraman, & Wood, 2007 ; Zhang et al, 2021 ), and virulence (Bommarius et al, 2013 ; Hirakawa et al, 2009 ). Interestingly, we previously found that indole decreases the virulence of vibrios belonging to the Harveyi clade towards gnotobiotic brine shrimp ( Artemia franciscana ) larvae and conventionally reared giant river prawn ( Macrobrachium rosenbergii ) larvae (Yang et al, 2017 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, indole also reduces E. coli biofilm formation ( Domka, Lee & Wood, 2006 ; Domka et al, 2007 ; Lee, Jayaraman & Wood, 2007 ). Moreover, indole was reported to increase the bacterial uptake of antimicrobials through an interaction with the Mtr permease ( Zhang, Yang & Defoirdt, 2022 ), and indole signaling is a valid target for the development of novel therapeutics in order to control infections caused by Harveyi clade vibrios in aquaculture ( Wu et al, 2022 ). These studies suggest that indole may benefit antibiotic treatment when combined with different antibiotics.…”
Section: Introductionmentioning
confidence: 99%